A Narrative Review of the Expression and Role of Nitric Oxide in Endometriosis - Seung Geun Yeo; Yeon Ju Oh; Jae Min Lee; Sung Soo Kim; Dong Choon Park (Antioxidants)
Nitric oxide (NO) is a key signaling molecule involved in cellular communication and plays a critical role in various biological processes. Given its dual role in the pathogenesis of endometriosis, we conducted a systematic literature review to explore its mechanisms further. Numerous studies have investigated the expression and role of NO in various diseases, including those in the field of gynecology. However, the expression and role of NO in endometriosis remain a topic of ongoing debate. Therefore, we conducted a comprehensive literature review using the Cochrane Library, EMBASE, Google Scholar, PubMed, and SCOPUS databases to evaluate the induction and role of NO in the pathogenesis of endometriosis. Of the 27 papers ultimately reviewed, 22 (81.4%) reported that NO contributes to the pathogenesis of endometriosis, 3 (11.1%) suggested that NO acts as a protective mechanism against endometriosis, and 2 studies (7.4%) found no association between NO and the pathogenesis of endometriosis. The expression and levels of NO in endometriosis were associated with pregnancy, infertility, menstruation, and pelvic pain. Research conducted on rats and mice demonstrated that NO, nNOS, eNOS, and iNOS play significant roles in the development of endometriosis. Most studies suggested that increased NO levels are associated with the pathogenesis of endometriosis.